Peningkatan Perilaku Kesehatan Gigi dan Mulut Anak Tunarungu Melalui Kegiatan Preventif dan Promotif Menggunakan Media Gambar Pop-Up - Hamdani, Riky; Hatta, Isnur; Setyawardhana, Raden Harry Dharmawan; Widodo, Widodo; Sitepu, Alexander; Azizah, Aulia (Jurnal Pengabdian ILUNG (Inovasi Lahan Basah Unggul), 2025)
Dental and oral health problems in deaf children are higher compared to other normal children. Based on statistical data from the Indonesian Ministry of National Education, the number of deaf children in Indonesia is quite high, reaching 0.17%. This shows that 17 children out of 10,000 preschool children up to the age of 12 years have hearing loss and speech limitations. This community service activity aims to improve the dental and oral health behavior of deaf children at SLB Negeri 2 Banjarmasin City using pop-up image media. The method used in this community service activity is to carry out promotive activities in the form of teacher training as educators for dental and oral health counseling using pop-up image media and health promotion using pop-up image media. Preventive activities carried out include conducting dental and oral health screenings and carrying out fissure sealant and atraumatic restorative treatment treatments based on the screening results. Evaluation of community service activities is carried out by measuring the results of the pretest and posttest of student knowledge and analyzing the provision of preventive actions for students at SLB Negeri 2 Banjarmasin City. The results of this community service show a difference in knowledge before and after health promotion interventions were given, as well as an increase in students' dental and oral health after preventive measures in the form of pit and fissure sealants and atraumatic restorative treatment. The use of educational media for children with disabilities, especially deaf children, is effective in increasing knowledge of dental and oral health so that it can improve the quality of life for deaf children